1998
DOI: 10.1017/s0022149x00016308
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological survey of Echinococcus granulosus and other helminths in animal populations in northern Israel

Abstract: In a survey carried out during the period May 1995 to November 1996, in communities of various ethnic groups in northern Israel, 206 dogs were examined for Echinococcus granulosus and other intestinal helminth parasites by arecoline hydrobromide purges and the coproantigen-ELISA. The arecoline test was performed close to the owners' homes, using plastic sheets secured to the ground. From 56 dogs examined in the Muslim town of Tamra, six (10.7%) were found to be infected with E. granulosus. Four of them also ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 17 publications
(7 reference statements)
1
11
1
Order By: Relevance
“…As the population of Jordan is predominantly Moslem, a major contributing factor in obtaining higher infection rates in Jordan compared to those in Tamra is the method of sampling. In the present series, dogs were necropsied while in the study carried out by Hoida et al (1998), dogs were sampled for intestinal helminthes by purging with arecoline hydrobromide and by coproantigen ELISA for E. granulosus. The latter methods are not as sensitive as the necropsy method particularly when dogs harbor light worm burdens (Deplazes et al 1992;Craig et al 1995).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As the population of Jordan is predominantly Moslem, a major contributing factor in obtaining higher infection rates in Jordan compared to those in Tamra is the method of sampling. In the present series, dogs were necropsied while in the study carried out by Hoida et al (1998), dogs were sampled for intestinal helminthes by purging with arecoline hydrobromide and by coproantigen ELISA for E. granulosus. The latter methods are not as sensitive as the necropsy method particularly when dogs harbor light worm burdens (Deplazes et al 1992;Craig et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The disease is endemic or highly endemic in Kuwait, Iraq, Syria, Lebanon, and Jordan (see reviews by Matossian et al 1977;Al-Yaman et al 1987;Kamhawi 1995;Abdel-Hafez and Kamhawi 1997). Cestodes, nematodes and acanthocephalans have been identi®ed in the intestines of stray and pet dogs as well as foxes in various countries including Jordan (Ajlouni et al 1984;Al-Tae et al 1988;Abo-Shehada and Ziyadeh 1991;Shastri 1991;Vanparijs et al 1991;Dalimi and Mobedi 1992;Deplazes et al 1992;Jones and Walters 1992a, b;Epe et al 1993;Saeki et al 1997;Hoida et al 1998).…”
Section: Introductionmentioning
confidence: 98%
“…Dogs act as the definitive host for several zoonotic diseases, including echinococcosis and toxocariasis (Schantz 1994). Both stray and pet dogs in Jordan and other Middle Eastern countries were found to be infected with cestodes, nematodes and acanthocephalans (Ajlouni et al 1984;Abo-Shehada and Ziyadeh 1991;Hoida et al 1998;El-Shehabi et al 1999. Echinococcus granulosus, the causative agent of cystic echinococcosis (CE), is of high prevalence among dogs in Jordan (El-Shehabi et al 1999 and nearby countries (Molan 1993;Hoida et al 1998;Haridy et al 2000).…”
Section: Introductionmentioning
confidence: 95%
“…A recent study from Israel and Palestine reported CE in 9% of sheep slaughtered in abattoirs in Nablus, Jenin and Tubas (El-Ibrahim, 2009). In the northern city of Tamra, 5.9% of 874 sheep and 5.3% of 616 goats were infected (Hoida et al, 1998). In neighbouring Yirka, 75% of sheep and goats were slaughtered at individual households with only 25% at a Yirka abattoir (Nahmias et al, 1991).…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%
“…In three independent studies in northern towns of Yirka and Tamra near the Lebanese border, 7.9%, 14.2% and 10.7% of dogs were found infected based on arecoline purgation (Nahmias et al, 1991;Furth et al, 1994;Hoida et al, 1998). In the latter study, despite 10.7% infection in 56 dogs belonging to Muslim and Druze communities, none of the 150 dogs' excrement from Jewish communities was found infected, underlining the significance of sociocultural parameters and animal husbandry systems in transmission of CE.…”
Section: U N C O R R E C T E D P R O O Fmentioning
confidence: 99%